Happiness of university students in new normal Malaysia: The role of mattering, optimism, and social support - ZeWai Foo; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2021)
Studies among students in higher education have established the sense of altering as one of the predictors of subjective well-being, which represents happiness. However, the transition from the quarantined period to the new normal lifestyle amidst the pandemic in Malaysia might have altered the way mattering predicts happiness. Some studies have reported that students tend to feel less socially supported during online studies, and not every one of them showed high optimism or the belief that a better situation will come soon. We hypothesized that in the new normal, the association between mattering and happiness is fully mediated by perceived social support and optimism. In order to test the hypothesis, 400 university students between 18 to 30 years of age were recruited to respond to the Satisfaction with Life Scale, Revised life orientation test, mattering to others questionnaire, and multidimensional scale of perceived social support. Analyses with Bootstrap method with 5,000 sampling and 95% confidence interval using PROCESS Macro Model 4 yielded results, which suggested that mattering is still a robust predictor of happiness and that both perceived social support and optimism only partially mediated the association. Limitations and suggestions for future studies are discussed.